On the multi-mode, multi-skill resource constrained project scheduling problem : a software application - Santos, Mónica A. (2011)
We consider an extension of the Resource-Constrained Project Scheduling Problem (RCPSP) to multi-level (or multi-mode) activities. Each activity must be allocated exactly one unit of each required resource and the resource unit may be used at any of its specified levels. The processing time of an activity is given by the maximum of the durations that would result from a specific allocation of resources. The objective is to find the optimal solution that minimizes the overall project cost which includes a penalty for tardiness beyond the specified delivery date as well as a bonus for early delivery. We give some of the most important solution details and we report on the preliminary results obtained. The implementation was designed using the C# language.